Understanding the Functional Properties of Neonatal Dendritic Cells: A Doorway to Enhance Vaccine Effectiveness? - Papaioannou, Nikos E.; Pasztoi, Maria; Schraml, Barbara U. (Frontiers in Immunology, 2019)
Increased susceptibility to infectious diseases is a hallmark of the neonatal period of life that is generally attributed to a relative immaturity of the immune system. Dendritic cells (DCs) are innate immune sentinels with vital roles in the initiation and orchestration of immune responses, thus, constituting a promising target for promoting neonatal immunity. However, as other immune cells, neonatal DCs have been suggested to be functionally immature compared to their adult counterparts. Here we review some of the unique aspects of neonatal DCs that shape immune responses in early life and speculate whether the functional properties of neonatal DCs could be exploited or manipulated to promote more effective vaccination in early life.